Boekbesprekings/Book reviews (HTS teologiese studies, 2008)
Seeking the favor of God, Vol 2: The development of penitential prayer in second temple Judaism Salvation and the cross Dimensions of evil: Contemporary perspectives The new perspective on Paul Viewed from the shoulders of God: Themes in science and theology Do you not remember? Scripture, story and exegesis in the rewritten Bible of Pseudo-Philo (Journal for the Study of the Pseudepigrapha Supplement Series (37) Judaism of the second temple period (Vol 1: Qumran and Apocalypticism) Galatians and the imperial cult Divorce and remarriage in the Bible: The social and literacy context Consuming Jesus: Beyond race and class divisions in a consumer church God en geweld in het Oude Testament The compassionate leader: Leading like Jesus did. How treating people properly can give you the corporate edge